"She Aims to Harass Him": Jewish Women in Muslim Legal Venues in Medieval Egypt. Issue 1 (20th April 2018) - Zinger, Oded
Abstract : Jewish women in medieval Egypt made extensive use of Muslim legal venues. By amassing and analyzing a sizable corpus of Geniza documents and contemporary responsa, this study explores how women accessed these venues, why they did so, and the response of the Jewish community. Complementing the traditional explanations given to Jewish use of Muslim legal venues, such as legal difference and greater enforceability, I argue that Muslim legal forums offered Jewish women a way of resisting the pressures they often faced in Jewish communal institutions and at home. For its part, the Jewish leadership used a variety of measures to prevent women from using Muslim legal venues; women who persisted were castigated more harshly than men were. This study also sheds light on Jewish women's points of contact with broader Islamic society and the relationship between Jews and the Islamic state.